Aging and Neuronal Vulnerability - Mattson, Mark P. (2006)
Everyone ages, but only some will acquire a neurodegenerative disorder in the process. Disease might occur when cells fail to respond adaptively to age-related increases in oxidative, metabolic and ionic stress resulting in excessive accumulation of damaged proteins, DNA and membranes. Determinants of neuronal vulnerability might include cell size and location, metabolism of disease-specific proteins, and repertoire of signal transduction pathways and stress resistance mechanisms. Emerging evidence on protein interaction networks that monitor and respond to the normal aging process suggests that successful neural aging is possible for most, but also cautions that cures for neurodegenerative disorders are unlikely in the near future.